Production and quality assurance of solid recovered fuels using Mechanical- Biological Treatment (MBT) of waste: a comprehensive assessment - Velis, C. A.; Longhurst, Philip J.; Drew, Gillian H.; Smith, Richard; Pollard, Simon J. T. (Taylor & Francis, 2010)
The move from disposal-led waste management to resource management demands an ability to map flows of the properties of waste. Here, we provide a comprehensive review of how mechanical-biological treatment (MBT) plants, and the unit processes that comprise them, perform in relation to management of material flows, while transforming inputs into output fractions. Focus is placed on the properties relating to the quality of MBT-derived fuels. Quality management initiatives for refuse-derived fuels (RDF) or solid recovered fuels (SRF) are reviewed and SRF quality from MBT plants is assessed through a statistical analysis of published data. This can provide a basis for a targeted reduction in pollution load from solid MBT outputs and subsequent end-user emissions. Our analysis, among else, (1) verifies the difficulty of chemical separation solely by mechanical means; (2) illustrates the trade-off between achieving a high quality of recoverable outputs and the quantity/properties of reject material; and (3) indicates that SRF quality could respond to legislative requirements and market needs, if specific improvements (reduction of Cl, Cu, and Pb content) are achieved. Further research could enhance the confidence in the ability of MBT plants to produce a quality-assured SRF suitable for specific end-users, without contradicting the wider requirement for an overall sustainable management of resources.
Keywords: material flow analysis mechanical-biological treatment refuse-derived fuel residual waste solid recovered fuel reliable data-analysis refuse-derived fuel air classification size-reduction comminution processes discrete materials element behavior particle-shape trommel model performance